Early weaning of kid goats does not compromise rumen microbial colonization and post-weaning digestive capacity - Yáñez Ruiz D.R.; Martínez E.; Jiménez E.; Serrano R.; Belanche A.; Martín García A.I. (Innovation for sustainability in sheep and goats, 2019)
Milk feeding in intensive dairy farming represents a significant cost, which can potentially be reduced if the animal is weaned early. However, an abrupt transition from milk to solid feed may affect animal’s growth, appropriate rumen development and future digestive capacity. This experiment was conducted to assess the effect of an early weaning (EW) practice (5 weeks of life) on rumen microbial colonization and post weaning digestive ability against the normal weaning (NW) practice in diary goats farming (7-8 weeks). Twelve new-born kid goats were used and randomly allocated to one of the two experimental groups (n=6). They were provided mothers colostrum for 24 hours and then taken away and fed commercial milk replacer following the manufacturer guidelines. Alfalfa hay and starter concentrate pellets were available from week one after birth. After weaning, animals were kept together until 6 months of life. Then rumen content samples were collected and a digestibility trial was conducted. The weights of kid goats did not differ EW and NW until month six of life and both groups experienced a temporal decline in weight gain during the 7-10 days after weaning (more pronounced in EW). The fermentation pattern and microbial biomass were not different between groups. At month six of life neither the fermentation pattern nor the apparent digestibility differ between groups. Our results suggest that an early weaning strategy is possible and does not compromise the future digestive efficiency of the animal.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)